Effect of Human Development Index (HDI), Gross Regional Domestic Product (PDRB), and Number of Labor Force on Poverty in North Sumatra Province - Selvia Margaretta Manalu; Nurlina; Miswar (Formosa Journal of Science and Technology, 2023)
This research aims to determine the influence of HDI, PDRB, and the Number of Labor Force on poverty absorption in the province of North Sumatra both simultaneously and partially in 2008-2023. This study uses time series data with multiple linear regression analysis methods using E-Views version 12 application. This research explains that partially, the human development index (HDI) variable has a negative and significant influence on poverty in North Sumatra Province, the gross regional domestic product (PDRB) variable has a negative and insignificant influence on poverty in North Sumatra Province, the variable number of labor force has a positive and insignificant influence. While simultaneously, the human development index (HDI), gross regional domestic product (PDRB) and the number of labor force simultaneously have a significant effect on poverty in North Sumatra Province.